2019
DOI: 10.2147/ndt.s184585
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of comorbid anxiety disorders in late-life depression: findings from geriatric tertiary outpatient settings

Abstract: PurposeThe study evaluated the prevalence of comorbid anxiety disorders in late-life depression (LLD) and identified their associated factors.Patients and methodsThis study involved 190 elderly Thais with depressive disorders diagnosed according to the Mini-International Neuropsychiatric Interview (MINI). Anxiety disorders were also diagnosed by the MINI. The 7-item Hamilton Depression Rating Scale (HAMD-7), Montreal Cognitive Assessment, Geriatric Depression Scale (GDS), Core Symptoms Index, Neuroticism Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
(35 reference statements)
3
4
0
4
Order By: Relevance
“…This finding suggests that it is worth including perceived stress as a variable in further studies exploring the relationship between neuroticism and cognition, whether they be cross-sectional or longitudinal. Previous studies have indicated the existence of the relationship between neuroticism, perceived stress, and depression in elderly people with clinical depressive disorder [55,56], and the present study supports the existence of such relationships among elderly people without clinically diagnosed depressive disorders. This might apply to the elderly at similar pre-operative periods (or in related clinical settings) as a means of mitigating the severity of depressive symptom, heightened perceived stress, or cognitive decline following operations which typically lead to increased morbidity or prolonged hospitalization [57].…”
Section: Discussionsupporting
confidence: 88%
“…This finding suggests that it is worth including perceived stress as a variable in further studies exploring the relationship between neuroticism and cognition, whether they be cross-sectional or longitudinal. Previous studies have indicated the existence of the relationship between neuroticism, perceived stress, and depression in elderly people with clinical depressive disorder [55,56], and the present study supports the existence of such relationships among elderly people without clinically diagnosed depressive disorders. This might apply to the elderly at similar pre-operative periods (or in related clinical settings) as a means of mitigating the severity of depressive symptom, heightened perceived stress, or cognitive decline following operations which typically lead to increased morbidity or prolonged hospitalization [57].…”
Section: Discussionsupporting
confidence: 88%
“…Investigators have supported the relationship between subjective complaints and feelings of stress and neuroticism [21]. In addition to perceived stress, neuroticism is closely related to anxiety and depression [43][44][45], that constitute high risk for worsening dry eye symptoms and poor QOL [5], but not included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Askotan bere aldetik ikertuak izan diren arren, depresioa zein antsietatea hertsiki erlazionatuta aurkitu dira. Hala, azterlan ezberdinek adierazi dute depresioa dutenen % 17-57k antsietate-nahasmenduren bat azaltzen duela eta, alderantziz, antsietatea dutenen % 13-28k aldibereko depresioa agertzen duela (Almeida et al, 2012;Beekman et al, 2000;Suradom et al, 2019;van Balkom et al, 2000). Komorbilitate hori dela-eta, nahasmendu zein sintoma depresibo eta antsiosoak ezberdintzeko gai diren neurriak garatzea garrantzitsua litzateke.…”
Section: Nondik Norakoakunclassified
“…Ikerketa pilotu honen bigarren helburua, antsietatearen, depresioaren eta bien arteko komorbilitatearen prebalentzien kalkuluari zegokion. Aurkitutako prebalentziek bat egiten dute adineko pertsona egoitzaratuen osasun mentala aztertu duten ikerketen emaitzekin, antsietatearen kasuan (Bryant et al, 2008), depresioaren kasuan (Azeem eta Naz, 2015;Franco eta Monforte, 1996), bai eta komorbilitatearen kasuan ere (Suradom et al, 2019;van Balkom et al, 2000). Komorbilitatearekin lotuta, ikerlan honen hirugarren helburua izan da miatzea ea GADEak antsietatearen eta depresioaren artean erlazio esanguratsurik antzematen duen.…”
Section: Eztabaidaunclassified
See 1 more Smart Citation